Synergising water and energy requirements to improve sustainability performance in mine tailings management - Adiansyah, J.; Rosano, Michele; Vink, S.; Keir, G.; Stokes, J. (Elsevier, 2016)
© 2016 Elsevier LtdMining is a water and energy intensive industry, and reducing water and energy consumption are two important issues in the quest for more sustainable industrial production. The aim of this paper is to assess the correlation between water and energy requirements in various tailings disposal strategies (on a per cent solids-based analysis). Two main methods are used: rheology testing and a system modelling approach. A coal mine site in Australia was chosen as a case study to apply five tailings disposal options. These five options are differentiated by the percentage of solids in the tailings ranging from 30% to 70%. The rheology analysis indicated that the coal mine tailings with 65–70% solids are not pumpable and these two options are beyond the scope of this study. The results of the analyses show that the optimal scheme process in terms of water saving, water management, and energy consumption involved tailings with 50% mass solids. The implementation of this option resulted in both lower water transport (15,532 ML/y) and energy consumption (34.7 TJ/y). This option also reduced the overall flows of water to the Tailings Storage Facility by 30%.